2002
DOI: 10.1021/jp0210576
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Energy Transfer in Highly Excited Bridged Azulene-Aryl Compounds:  Direct Observation of Energy Flow through Aliphatic Chains and into the Solvent

Abstract: Intra- and intermolecular vibrational energy flow in vibrationally highly excited bridged azulene-(CH2) n -aryl (n = 0,1,3; aryl = benzene or anthracene) compounds is observed using time-resolved pump−probe laser spectroscopy. Light absorption in the azulene S1-band, followed by fast internal conversion, leads to vibrational excitation at the azulene side of the molecules. Subsequent energy flow through the aliphatic chain to the aryl group at the other side of the molecules and vibrational energy transfer int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
96
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(102 citation statements)
references
References 58 publications
(102 reference statements)
5
96
0
1
Order By: Relevance
“…This time constant is much longer than the τ 3 value observed in the present study, 1.8 -4.9 ps, even taking the difference in the electronic states, S 0 and S 1 , into account. It is also noted that Schwarzer et al reported the intramolecular energy transfer rate of 1.2 -4 ps and the VET rate of 21 ps for electronically excited linked azulene-aryl compounds [25].…”
Section: Resultsmentioning
confidence: 92%
“…This time constant is much longer than the τ 3 value observed in the present study, 1.8 -4.9 ps, even taking the difference in the electronic states, S 0 and S 1 , into account. It is also noted that Schwarzer et al reported the intramolecular energy transfer rate of 1.2 -4 ps and the VET rate of 21 ps for electronically excited linked azulene-aryl compounds [25].…”
Section: Resultsmentioning
confidence: 92%
“…800-K transient temperature gradient was found by Dlott and coworkers in self-assembled monolayers of alkanes at a gold surface (26,27). A ballistic contribution to energy transport was reported for single-wall carbon nanotubes (28) and for several other systems (29)(30)(31).In this paper we use RA 2DIR spectroscopy to investigate the energy transport and dissipation in a series of PEG oligomers featuring an azido moiety and succinimide ester at two ends of the oligomer. The cross-peaks among N ≡ N and several other stretching modes, including three C ¼ O, and C-N-C modes were measured and analyzed.…”
mentioning
confidence: 88%
“…8,24 Pump-probe experiments directly observe energy flow within and out of a molecule by exciting a nonstationary vibrational state with one laser pulse and then probing the evolution of the system as a function of time with a second pulse. 25,26 Infrared absorption, [27][28][29][30][31][32] anti-Stokes Raman scattering, [33][34][35][36][37] and ultraviolet absorption [38][39][40][41][42][43][44][45][46][47][48][49] are the most common methods for probing the vibrational dynamics in the ground electronic state and are generally most useful in the condensed phase where it is possible to obtain a high density of vibrationally excited molecules. In fact, there are relatively few timeresolved studies of IVR in the ground electronic state for gas phase systems.…”
Section: Introductionmentioning
confidence: 99%